THEORETICAL CALCULATION OF PRESSURE IN TANKS FILLED WITH DISCRETE MEDIUM - Vladimir B. Fedoseyev; Anastasiya B. Gordeyeva; Irina A. Zatsarinnaya (Advanced Engineering Research)
The vertical and horizontal distribution of free-flowing material pressure components is analyzed. The availability of the full pressure zone in the general tanker is shown. The expression for the lateral factor is derived on the basis of the equilibrium condition analysis.